Fukushimura BrainBank Project, Japan. (December 2021) - Kaneda, Daita; Yoshio, Hashizume; Yamamoto, Sakon; Ogawa, Norihiro; Kanesaka, Takeshi; Hishida, Chie; Yamamoto, Takayuki
Abstract: Background: The Fukushimura(welfare village), located in Toyohashi city, Japan, is a unique complex of various nursing home facilities including dementia homes, Day‐care houses, homes for disabled and mentally retarded, and the Fukushimura Hospital. This village is totally managed by private sector, the Sawarabi Medical Cooperative. About 800 elderly people reside in this area. The hospital plays a pivotal role within the village and acts as the central facility for each nursing homes. About 30 autopsies were conducted in a year. Most of the patients had dementia or chronic devastating cerebrovascular diseases. Moreover, geriatric residents with mentally retarted patients from their childhood were included. Because the brain banking in Japan is legally based on autopsy, Fukusimura BrainBank was established in the hospital from 1990. Our research institute was approved in 2004 by the Ministry of Education, Culture, Sports, Science and Technology, as one of the non‐govermental institutes which is permitted to apply for governmental grants. Method: For collecting samples, the brains are separated into two hemispheres, one for neuropathological analyses by using several antibodies for beta‐amyloid, phosphorylated tau, alpha‐synuclein, and TDP‐ 43. Modified gallyas‐silver staining was applied for evaluating argyrophilic grain disease. The neuropathological investigation was initially conducted by Kenji Kosaka, the founder of cortical Lewy bodies. The other hemispheres are stored for frozen sections. Other organs including retina has been collected. All the medical records and radiological images from the nursing home to hospital periods are stored in the research institute, which make it possible for the researchers to access the psychological symptoms in the long duration of the disease. The database share the same coding system for Japanese Brain Bank Network for Neuroscience Research (JBBNNR). Result: At the end of 2020, more than 776 cases of frozen brains are stored in FBB. We already have over 20 collaborators and supply our samples for more than 30 research institutes in Japan. Conclusion: FBB plays a unique and important role for the people with nursing home residentials in Japan.